Sonochemical-assisted fabrication of biologically active chiral poly(ester-imide)/TiO2 bionanocomposites derived from L-methionine and L-tyrosine amino acids (eXPRESS Polymer Letters)
A new chiral poly(ester-imide) (PEI) was prepared via direct polyesterification of N,N'-(pyromellitoyl)-bis-(Ltyrosine dimethyl ester) and N-trimellitylimido-L-methionine using tosyl chloride/pyridine/N,N'-dimethylformamide system as a condensing agent. The resulting new chiral polymer was obtained in good yield and had good thermal stability as well as good solubility in common organic solvents. After that, PEI/titanium bionanocomposites (PEI/TiO2 BNCs) were prepared using the modified nanosized TiO2 via sonochemical reaction that can accelerate hydrolysis, increase collision chance for the reactive system and improve the dispersion of the nanoparticles in polymer matrix. The scanning electron microscopy (SEM), field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) results indicated that there is no aggregation of a large quantity of particles. Thermogravimetric analysis (TGA) confirmed that the heat stability of the BNC polymers in the temperature range of 400–800ºC was enhanced by addition of TiO2 nanoparticles. Furthermore, in vitro toxicity test was employed for assessing the sensitivity of these compounds to microbial degradation. To this purpose, polymer and PEI/TiO2 BNCs were investigated under soil burial conditions. The results of this study revealed that polymer and its BNCs are biologically active and non-toxic in the natural environment although some antimicrobial properties were found for BNCs.